Improving Technological Pedagogical Content Knowledge (TPACK) of Elementary School Teachers through Training with a Collaborative, Practical and Reflective Approach - Rahayu, Ai Hayati; Widodo, Ari; Saud, Udin Syaefudin; Muslim, Muslim (Universitas Pendidikan Indonesia, 2024)
The integration of technology into teaching and learning processes is highly relevant in today’s educational landscape, as technology has become essential for facilitating student learning. However, in practice, technology has not been fully optimized to develop students' critical thinking skills. The TPACK framework, which guides teachers in integrating technology into the learning process, must be continuously refined through relevant strategies. This study aims to describe how elementary school teachers' TPACK can be improved through collaborative, practical, and reflective approaches. A mixed methods design with an embedded experimental approach was employed. The study involved 84 teacher participants, randomly assigned to experimental and control groups. Data were collected using a 21st-century TPACK questionnaire and interviews. The findings indicate that collaborative, practical, and reflective approaches significantly enhanced elementary school teachers' TPACK. Statistical tests revealed a significant difference between the experimental and control groups, with the experimental group achieving higher average TPACK scores. Training that incorporates teacher collaboration, real-world classroom practices, and self-reflection effectively enhanced Technological Pedagogical Knowledge (TPK), contributing to the overall improvement of TPACK.